Self-assembled hybrid hydrogel microspheres create a bone marrow-mimicking niche for bone regeneration - Zhi He; Peilun Hu; Zifan Li; Kaige Mao; Jingchuan Zheng; Chun-Yi Yang; Yuyang Luo; Jia Yang; Zheng Cao; Jingsong Lu; Xiaobin Luo; Sengpav Tong; et al. (Bioactive Materials)
Bone marrow (BM), a natural niche rich in growth factors and bone marrow mesenchymal stem cells (BMSCs), provides an optimal regenerative microenvironment and is widely used in clinical applications. However, the limited proliferative capacity of BMSCs and the mismatch between bone regeneration and growth factors release constrain their effectiveness in treating critical bone defects. Drawing inspiration from the regenerative properties of BM, we developed self-assembled hybrid microspheres to replicate its function and address these challenges through a tissue engineering approach. This BM-mimicking niche enriched BMSCs via fast-degrading gelatin methacryloyl (GelMA) microspheres, which were loaded with exogenous BMSCs and conjugated with stem cell homing peptides (SKP) to recruit endogenous BMSCs. SKP further enhanced the stemness of BMSCs, thereby promoting angiogenesis and resolving inflammation. Slow-degrading chitosan methacryloyl (ChitoMA) microspheres facilitated sustained release of angiogenic (KLT) and osteogenic (OGP) peptides, supporting blood vessel maturation and osteogenesis. The early release of BMSCs and SKP, followed by the subsequent release of OGP and KLT, aligned with the dynamic process of bone regeneration. In a rat critical femoral condyle defect model, the BM-mimicking niche formed an in-situ ossification center, significantly enhancing bone regeneration. This study introduces a novel BM-mimicking niche characterized by a BMSC-enriched environment and the sequential release of therapeutic factors, offering a promising strategy for treating critical bone defects.